Outage Probability Performance of Hybrid Time-Power Splitting Relaying Protocol with Interferers Presence - Damilare Oluwole Akande; Olasunkanmi Fatai Oseni; Festus Kehinde Ojo; Job Adedamola Adeleke; Ayobami Olatunde Fawole (ABUAD Journal of Engineering Research and Development)
Combining simultaneous wireless information and power transfer with full-duplex communication at the energy-constrained relay terminal is a practical way of improving the lifespan and data rates performance of cooperative wireless networks. However, employing the two most common radio frequency energy harvesting protocols namely: time-switching and power splitting in full duplex mode is limited in outage probability performance for 5G network and beyond. The deployment of hybrid time-power splitting relaying protocol in full-duplex mode with decodes and forward relaying is a promising solution to energy-constrained relay devices. This paper analyses the outage probability of a decode and forward, full-duplex hybrid time-power splitting relaying protocol over Rayleigh fading channel with interfering signals considered at the destination. A mathematical expression for the proposed protocol's outage probability is derived, and simulation is performed in MATLAB. The simulations explore the impact of system parameters on outage probability, demonstrating the proposed protocol's advantage over the full-duplex power splitting relaying protocol. The result obtained showed that the proposed decode and forward, full-duplex hybrid time-power splitting relaying protocol outperformed the full-duplex power splitting relaying protocol by 8.89% and 50% at signal to noise ratio of 10dB and 25dB, respectively with maximum number of interferes.